Effect Observation on Repetitive Transcranial Magnetic Stimulation at Scalp Acupoints on Spastic Hemiplegia of Upper Extremity after Stroke - Yin QIN; Donge HUANG; Guohui KANG; Yue LIU; Munan LIN (康复学报)
Objective:To observe the clinical effect of repetitive transcranial magnetic stimulation (rTMS) at scalp acupoints on spastic hemiplegia of upper extremity after stroke.Methods:A total of 60 patients with spastic hemiplegia of upper extremity after stroke were randomly divided into control group, scalp-acupuncture group and rTMS acupoint group, with 20 cases in each group. The control group was treated by routine rehabilitation treatment; the scalp-acupuncture group was treated with scalp acupuncture on the basis of the control group, needling the stimulation area of the contralateral anterior parietal-temporal oblique line, posterior parietal-temporal oblique line and suboccipital side line;the rTMS acupoint group was treated with rTMS via scalp acupoint on the basis treatment of the control group, using rTMS to stimulate the ipsilateral Zhengying acupoint and Baihui acupoint.The three groups were treated once a day, five times in a week, continuous treatment for eight weeks.Modified ashworth scale (MAS) was used to assess the degree of spasticity of elbow joint on hemiplegic side; Fugl-Meyer upper extremity motor function scale (FMA-UE) was used to evaluate the recovery of motor function of spastic upper extremity;and modified Barthel index (MBI) was used to evaluate the activity of daily living.Results:After treatment for eight weeks, the scores of MAS, FMA-UE and MBI in the three groups improved significantly than those of treatment before, with statistically significant differences (P<0.05); Compared with the control group, the scores of MAS in scalp acupuncture group and rTMS scalp acupoint group decreased significantly, while the scores of FMA-UE and MBI increased significantly, with statistically significant differences (P<0.05).Conclusion:Repeated transcranial stimulation at scalp acupoints can promote the recovery of neurological function and improve the activity of upper extremity of stroke patients with spastic hemiplegia.